Pengaruh Kepemimpinan Transformasional, Motivasi, dan Pemberdayaan terhadap Kepuasan Kerja Karyawan pada Kantor Pertanahan Kota Semarang - Mudi Wardana, Dicky; Tristiana Rijanti S (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of transformational leadership, motivation, and empowerment on employee job satisfaction at the Semarang City Land Office. The research method used a quantitative approach with purposive sampling technique, where primary data were obtained by distributing questionnaires to 75 employees from a total population of 110 people. Data analysis was performed using multiple linear regression analysis with the help of SPSS version 26.0 to test the partial and simultaneous effects between variables. The results showed that transformational leadership, motivation, and empowerment partially had a positive and significant effect on employee job satisfaction with significance values ​​of 0.014, 0.009, and 0.005 (<0.05), respectively. Simultaneously, these three variables also had a significant effect on job satisfaction with an F-value of 25.908 and a significance level of 0.000 (<0.05), and an Adjusted R-square value of 0.502, meaning that 50.2% of the variation in job satisfaction was explained by these three independent variables. The conclusion of this study is that the better the transformational leadership, the higher the work motivation, and the more optimal the employee empowerment, the higher the job satisfaction level of employees at the Semarang City Land Office. Keywords: Transformational Leadership, Motivation, Empowerment, Job Satisfaction